A new reliable laboratory test of endurance performance for road cyclists - Schabort, E. J.; Hawley, J. A.; Hopkins, W. G.; Mujika, I.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: The purpose of this study was to devise and evaluate a laboratory test of cycling performance that simulates the variable power demands of competitive road racing. The test is a 100-km time trial interspersed with four 1-km and four 4-km sprints. METHODS: On three occasions separated by 5-7 d, eight endurance-trained cyclists (peak oxygen uptake 5.0 +/- 0.7 L.min-1, peak power output 411 +/- 43 W, mean +/- SD) performed the test on their own bikes mounted on an air-braked Kingcycle ergometer. Subjects were free to regulate their power output but were asked to complete each sprint and the full distance as quickly as possible. The only feedback given to the cyclists during each test was elapsed distance. RESULTS: In the first test, time for the 100 km and mean times for the 1-km and 4-km sprints were 151:42 +/- 10:36, 1:16 +/- 0:06, and 5:31 +/- 0:16 min:s, respectively; these times improved by 1.6-2.2% in the second test, but there was little further improvement in the third test (0.7 to -0.5%). The between-test correlation for 100-km time was 0.93 (95% CI 0.79 to 0.98), and the within-cyclist coefficient of variation was 1.7% (95% CI 1.1 to 2.5%). Mean sprint performance showed similar good reliability (within-subject variation and correlations for the 1-km and 4-km sprint times of 1.9%, 2.0%, 0.93, and 0.81, respectively). CONCLUSIONS: The high reliability of this laboratory test will make the test useful for research on performance of competitive road cyclists.